Polarimetric Imaging Through Scattering Media: A Review - Li, Xiaobo; Han, Yilin; Wang, Hongyuan; Liu, Tiegen; Chen, Shih-Chi; Hu, Haofeng (Frontiers in Physics, 2022)
Imaging in scattering media has been a challenging and important subject in optical science. In scattering media, the image quality is often severely degraded by the scattering and absorption effects owing to the small particles and the resulting nonuniform distribution of the intensity or polarization properties. In this paper, we review the recent development in polarimetric imaging techniques that address these challenges. Specifically, based on the polarization properties of the backscattering light, polarimetric methods can estimate the intensity level of the backscattering and the transmittance of the media, and also separate the target signal from the undesired ones to achieve high-quality imaging. In addition, the different designs of the polarimetric imaging systems offer additional metrics, e.g., the degree/angle of polarization, to recover images with high fidelity. We first introduce the physical degradation models in scattering media, and secondly, apply the models in different polarimetric imaging systems such as polarization difference, Stokes vector, Mueller matrix, and deep learning-based systems. Lastly, we provide a model selection guideline and future research directions in polarimetric imaging.